THE ROLE OF MUSICAL ART IN IMPROVING THE SPIRITUAL, MORAL AND AESTHETIC WORLDVIEW OF YOUTH OF NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
We are living in the era of globalization, in which it is important to constantly analyze the issue of spiritual-ethical-aesthetic education in raising the spiritual worldview of young people. In this article, the issues of using the opportunities of musical art to improve the spiritual-ethical-aesthetic education of the youth of New Uzbekistan, and to educate mentally mature personnel by widely promoting the concept of cultural and musical heritage in the era of globalization, when their worldview is being formed, are raised.